FRAMING BERITA PROMOSI PARIWISAT VS BERITA DAMPAK EKOLOGI PARIWISTA LOMBOK DI MEDIA MASSA (Analisis Framing Berita Promosi Pariwisata vs Berita Dampak Ekologi Pariwisata Lombok di Harian Lombok Post Januari-Desember 2014) - DIYAH INDIYATI; Dian Lestari Miharja; Hartin Nur Khusnia; Eka Putri Paramita (JCommsci - Journal Of Media and Communication Science, 2018)
In recent years the popularity of Lombok, West Nusa Tenggara as one of the foremost tourist destinations Indonesia indeed increasing. Lombok gains its popularity mostly supported by the social media and the mass media that present a variety of publications related to tourist sites, cultural attractions, events and other things that are considered attractive, presented either in news, photos, as well as freelance articles and travel-blog. This research y aims to determine how the media framing the news, especially the local media Lombok Post on Lombok tourism issue and whether the local media also do framing the news related to the impact of tourism. This research use Lombok Post publications during January 1st to December 31th 2014. This study uses framing analysis, by selecting the news published in this period by using Entman framing analysis which are done in four ways; problem identification, causal interpretatio), moral judgment, and suggestions deal with the problem (suggest remedies). According to its function, the role of mass media as a medium of informations, has played important and significant role in the case of Lombok tourism promotion. However, the media also should not to forget its education functions related to the impact of the tourism industry, particularly the ecological impacts arising from tourism activities.This research shows that fLombok Post frame its publications mostly to support Lombok’s tourism through issues selections and salience of the content mostly presents promotive topics.